INDEPENDENT STUDY AS A RESPONSE TO THE CHALLENGES OF COMPETENCEBASED TRANSFORMATION OF HIGHER EDUCATION (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the institutional, regulatory, and conceptual foundations for the introduction ofindependent student work within the higher education system of Uzbekistan. Particular emphasis isplaced on its role in developing the professional competence of technical university students. It isshown that independent work is not a supplementary form of learning, but a key tool for fosteringprofession-oriented skills such as responsibility, critical thinking, self-organization, and the ability toapply knowledge in uncertain real-life conditions. The article concludes that the adoption ofindependent work practices is closely linked to the integration of national education into the BolognaProcess and the ECTS system, which emphasize student-centered and outcome-based learning.